COMPOSITIONAL DISTINCTION BETWEEN OCEANIC AND CRATONIC LITHOSPHERE - Boyd F.R. (My University, 1989)
Modal and chemical data for variably-depleted peridotites of oceanic origin together with estimates of the composition of fertile parental peridotite are used to define an oceanic trend. This trend is most clearly illustrated in a plot of modal olivine against mg number. The oceanic residues represented by abyssal peridotites, ophiolite tectonites and some alpine peridotites are characteristically olivine-rich with mg numbers of 90.5–91.5. In contrast, peridotite xenoliths with equilibration temperatures below 1100–1200°C from the Archaean Kaapvaal craton in southern Africa are more enstatite-rich with mg numbers of 91.5–93.5. The structures and compositional relations of other Archaean cratons are believed to be similar to the Kaapvaal on the basis of tectonic, geophysical and sparse petrological data.Oceanic residues may have formed in a variety of tectonic environments, but are believed to be of relatively shallow origin. Mg-rich peridotite xenoliths from mafic volcanics erupted in continental areas marginal to Archaean cratons have compositions that fit the oceanic trend. Some of these xenoliths may be derived from oceanic lithosphere that has been accreted to Archaean nuclei. Others may have originated in sub-continental magmatic events at relatively shallow depths, comparable to those at which lithosphere has formed beneath the oceans. The Archaean cratonic peridotites have had a history that differs from those forming oceanic lithosphere and it is conjectured that they are high-pressure residues of komatiite formation. The cratonic peridotites have a lesser density than other peridotites and they are believed to have floated and coalesced to form continental nuclei.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей